Proceedings of the 2008 Symposium on Eye Tracking Research &Amp; Applications - ETRA '08 2008
DOI: 10.1145/1344471.1344489
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the task-evoked pupillary response with a remote eye tracker

Abstract: The pupil-measuring capability of video eye trackers can detect the task-evoked pupillary response: subtle changes in pupil size which indicate cognitive load. We performed several experiments to measure cognitive load using a remote video eye tracker, which demonstrate two extensions to current research in this area. First, we show that cognitive pupillometry can be extended from headmounted to remote eye tracking systems. Second, we demonstrate the feasibility of a more fine-grained approach to analyzing pup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
132
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(140 citation statements)
references
References 8 publications
6
132
0
2
Order By: Relevance
“…A valid and reliable assessment method of workload could be helpful in the optimization of systems that involve human-computer interaction, such as vehicles, computers, and simulators. One promising method for measuring workload is pupillometry, which is the measurement of the pupil diameter (e.g., Goldinger & Papesh, 2012;Granholm & Steinhauer, 2004;Klingner, Kumar & Hanrahan, 2008;Laeng, Sirois & Gredebäck, 2012;Marshall, 2007;Palinko et al, 2010;Schwalm, Keinath & Zimmer, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A valid and reliable assessment method of workload could be helpful in the optimization of systems that involve human-computer interaction, such as vehicles, computers, and simulators. One promising method for measuring workload is pupillometry, which is the measurement of the pupil diameter (e.g., Goldinger & Papesh, 2012;Granholm & Steinhauer, 2004;Klingner, Kumar & Hanrahan, 2008;Laeng, Sirois & Gredebäck, 2012;Marshall, 2007;Palinko et al, 2010;Schwalm, Keinath & Zimmer, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of gaze direction on the measured pupil size is another issue. Where Pomplun & Sunkara (2003) reported a systematic dependence of pupil size on gaze direction, Klingner, Kumar & Hanrahan (2008) argued that the ellipse-fitting method for the estimation of the pupil size is not affected by perspective distortion.…”
Section: Introductionmentioning
confidence: 99%
“…Pupil diameter is of interest due to the fact that when people are faced with a challenging cognitive task, their pupils dilate. This phenomenon is called the Task Evoked Pupillary Response (TEPR) (Beatty, 1982;Klingner et al, 2008). However, cognitive load is certainly not the only factor influencing pupil diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Using a remote eye tracker Klingner et al (2008) successfully estimated cognitive load in a desktop environment, while our group did so in a driving simulator (Palinko et al, 2010). However, neither study explored the interaction between cognitive load and the pupil's light reflex, opting instead to maintain near-constant lighting.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental results indicated that the fluctuation rhythm of the pupil area could be used as an effective physiological index to evaluate mental workload. Klingner et al (2008) examined the pupil measuring capability of video based eye tracker for cognitive workload evaluation. In the experiment of several tasks including arithmetic and memory ones, subtle changes of pupil size in the task-evoked pupillary response were detected using remote eye tracker.…”
Section: Correlation To Workload In Arithmetic/memory Taskmentioning
confidence: 99%